Bipolar Personality Disorder of Pat Solitano Jr. In David Owen Russell’s “Silver Linings Playbook” (2012) - Cita Resmi; Latifah Dwi Ariyani (Metaphor, 2023)
This article presents the study result of : (1)bipolar disorder indications reflected in the main character of Pat Solitano in “Silver Linings Playbook”, (2) the main character’s mental state as the sufferer of bipolar disorder presented in “Silver Linings Playbook”. The study uses a descriptive qualitative method to analyze the film entitled “Silver Linings Playbook” directed by David Owen Russel as the objective research. The collecting data of the research method includes watching and reading, identifying, classifying, and selecting. The analyzing data of the research method by using displaying, explaining, and interpreting. The researcher analyzes the data by using Abnormal Psychology and Sigmund Freud Psychoanalysis. The result of the study : (1) the type of bipolar disorder reflected in the main character in David O. Russell’s in “Silver Linings Playbook” such as mood swing, irritability and agitation, impulsive behavior, grandiosity and racing thought, and sleep disturbance; (2) the psychological condition of Pat as bipolar disorder sufferer in form manic episodes are pat became a grumpy character, easily agitated, impulsive, narcissistic, and an insomniac.